THE EFFECT OF INDIVIDUAL, GROUP AND TEAM WORK BEHAVIOR TOWARD TEACHER PERFORMANCE IN SMAN 3 MEDAN - Rizki Akmalia; Amiruddin Siahaan; Mesiono Mesiono (UIN Sumatera Utara Medan, 2020)
This study investigates (1) The influence of Individual Behavior TowardTeacher Performance in SMA 3 Medan; (2) The Influence of Group Behavior on Teacher Performance in SMA 3 Medan; (3) The Influence of team work on Teacher Performance in SMA 3 Medan; (4) the influence among Individual, Group and Team Work behavior toward Teacher Performance in SMA Negeri 3 Medan. The results of the study shows that (1) There is a positive and significant influence between X1 to Y 0.9%. It meant that if individual teacher's behavior is getting better in teaching, it will be followed by the increasing of teacher performance in doing their main tasks; (2) There is a positive and significant effect between X2 and Y 7.1%. It is meant that if the behavior of a teacher group in SMA Negeri 3 Medan gives a good example for students, teachers, and the school environment, it will be followed by the increasing of teacher performance in teaching learning process (3) there is a negative effect between X3 to Y -0.9%. It can be said that if the work team is good and solid it will not affect the improvement of teacher performance; (4) there is a positive and significant influence between X1, X2, and X3 together with Y, the correlation coefficient value is 0.303, R Square 0.092 and Adjusted R Square 0.057. It shows that the influence of X1, X2, and X3 to Y is 5.7% and the remaining 94.3% is influenced by other factors from variables not included in this study.